The Entner-Doudoroff Pathway Is Obligatory for Gluconate Utilization and Contributes to the Pathogenicity of Vibrio cholerae - Patra, Tapas (American Society for Microbiology, 2012)
The Entner-Doudoroff (ED) pathway has recently been shown to play an important role in sugar catabolism for many organisms although very little information is available on the functionality of this pathway in Vibrio cholerae, the causative agent of cholera. In this study, activation of the genes edd and eda, encoding 6-phosphogluconate dehydratase and 2-keto-3-deoxy-6-phosphogluconate aldolase, was used as a marker of a functional ED pathway in V. cholerae. Transcriptional activation analyses and gene silencing experiments with cells grown in sugar-supplemented M9 medium demonstrated that the ED pathway is functional in V. cholerae and is obligatory for gluconate catabolism. Importantly, selective activation of the ED pathway led to concurrent elevation of transcripts of prime virulence genes (ctxA and tcpA) and their regulator (toxT). Further, lowering of these transcript levels and cholera toxin production in vitro by an ED pathway-defective mutant (strain N16961 with a Δedd mutation [Δedd(N16961) strain]) suggested the importance of this pathway in regulating V. cholerae virulence. The in vivo relevance of these data was established as the mutant failed to colonize in suckling mice intestine or to induce fluid accumulation in ligated rabbit ileal loops. Activation of the ED pathway in V. cholerae was shown to inhibit biofilm formation in vitro that could be reversed in the mutant. As further support for these results, comparative transcriptome analysis with cells grown in the presence of glucose or gluconate revealed that a functional ED pathway led to activation of a subset of previously reported in vivo expressed genes. All of these results suggest the importance of the ED pathway in V. cholerae pathogenesis.